Food Name Translation Practice: A Case Study of Indonesian–English Menus - Retno Wulandari Setyaningsih (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
This paper analyzed the translation practice on chained hotel restaurant menus, especially on Indonesian traditional menu into English. The translation of food names requires translators to consider both the cultural associations embedded in the names, their meaning and function in the source language (SL) as well as the translatability of the terms in the target language (TL). Employing Descriptive Translation Studies, 33 Indonesian traditional food names from five hotel restaurants in Surabaya are analyzed in order to reveal the common practice of Indonesian traditional food name (SL) into English (TL). Out of 33 data, there are 21 traditional food name translation compared and elaborated using Descriptive Translation Studies approach. The translation procedures identified then are grouped based on Kwiecinski. The result indicated that exoticizing procedures only constitute of 9.5%, while rich explicatory procedures accounts for 61.9%. Further, recognized exoticism procedures was found in one data or 4.8%, and assimilative procedures are applied in five data or 23.8%. Thus, the most common practice in translating Indonesian traditional food names into English is mostly by describing the appearance of food completed by a list of side dishes and condiments. Thus, there is an attempt to generalize the unique feature of traditional food which may help target readers to recognize the food. However, the long information provided rarely explains the taste, and weights more into the serving appearance of the traditional food, reducing the potent of introducing the identity of Indonesian traditional food.